2019
DOI: 10.1130/g45831.1
|View full text |Cite
|
Sign up to set email alerts
|

The meteorite flux of the past 2 m.y. recorded in the Atacama Desert

Abstract: The evolution of the meteorite flux to the Earth can be studied by determining the terrestrial ages of meteorite collected in hot deserts. We have measured the terrestrial ages of 54 stony meteorites from the El Médano area, in the Atacama Desert, using the cosmogenic nuclide 2 36 Cl. With an average age of 710 ka, this collection is the oldest collection of non fossil meteorites at the Earth's surface. This allows both determining the average meteorite flux intensity over the last 2 Myr (222 meteorites larger… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 33 publications
(49 reference statements)
1
32
2
Order By: Relevance
“…This order of magnitude is consistent with flux reported by Bland et al (1996) with 159 events per year per 1 million km 2 (>20 g). It is also similar to the flux calculated by Halliday et al (1989) with 100 meteorites per year per 1 million km 2 (>10 g) based on meteor detections and mathematics calculation model, as well as the flux estimated by Drouard et al (2019) with 222 meteorites larger than 10 g per km 2 per Myr.…”
Section: Dca Name Countrysupporting
confidence: 85%
See 1 more Smart Citation
“…This order of magnitude is consistent with flux reported by Bland et al (1996) with 159 events per year per 1 million km 2 (>20 g). It is also similar to the flux calculated by Halliday et al (1989) with 100 meteorites per year per 1 million km 2 (>10 g) based on meteor detections and mathematics calculation model, as well as the flux estimated by Drouard et al (2019) with 222 meteorites larger than 10 g per km 2 per Myr.…”
Section: Dca Name Countrysupporting
confidence: 85%
“…() with 100 meteorites per year per 1 million km 2 (>10 g) based on meteor detections and mathematics calculation model, as well as the flux estimated by Drouard et al. () with 222 meteorites larger than 10 g per km 2 perMyr.…”
Section: Discussionmentioning
confidence: 96%
“…Caleta el Cobre 022 was found casually by tourists traveling in the Atacama Desert, Chile, in November 2016, lying at the surface in the CeC dense collection area, which is part of the densest meteorite collection area in hot deserts (Hutzler et al 2016;Drouard et al 2019). It is a single stone, almost fully crusted.…”
Section: General Description and Physical Propertiesmentioning
confidence: 99%
“…However, shifting the discussion to the meteorites, other interesting data can be found. In fact, Zolensky et al (2006) provided a total mass flux to Earth (in the meteorite weight range 10 g–10 6 g) of 5.38·10 4 kg yr –1 whereas Drouard et al (2019) found a flux of 222 meteorites (>10 g) per km 2 per m.y. According to these data, over an area of 59,000 km 2 , that is the area covered by Obsequens’s events (Fig.…”
Section: Discussionmentioning
confidence: 99%